Designing to Promote Access, Quality, and Student Support in an Advanced Certificate Programme for Rural Teachers in South Africa - Fresen, Jill W.; Hendrikz, Johan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This paper reports on the re-design of the Advanced Certificate in Education (ACE) programme, which is offered by the University of Pretoria through distance education (DE) to teachers in rural South Africa. In 2007, a team re-designed the programme with the goal of promoting access, quality, and student support. The team included an independent body, the South African Institute of Distance Education (SAIDE), and various education specialists. Training workshops for academics and a comprehensive internal and external review process contributed to the quality of the re-designed programme. Interactive web-based technologies were not included because of poor Internet connectivity; however, the authors note the use and potential of cell phone technology for DE programmes. Student support was enhanced by an additional short contact session, a capping assignment, a CD-ROM, and decentralised tutoring at contact venues. The programme was re-evaluated and approved in 2008, and the re-design methodology now guides similar projects.